1993
DOI: 10.4148/1051-0834.1444
|View full text |Cite
|
Sign up to set email alerts
|

Graduate Education in Agricultural Communication: The Need and Role

Abstract: Is there a meed for graduate studies in agricultural communication?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Several authors have addressed education in agricultural communications (e.g., Adams, 1922;Boone, Paulson, & Barrick, 1993;Elefson, 1992;Reisner, 1990b) and the workplace skills graduates need (e.g., Morgan, 2012). Sprecker and Rudd (1998) reported that "communication skills … are more important than subject-area knowledge" (p. 31) when preparing students for agricultural communications.…”
Section: Agricultural Communications Educationmentioning
confidence: 99%
“…Several authors have addressed education in agricultural communications (e.g., Adams, 1922;Boone, Paulson, & Barrick, 1993;Elefson, 1992;Reisner, 1990b) and the workplace skills graduates need (e.g., Morgan, 2012). Sprecker and Rudd (1998) reported that "communication skills … are more important than subject-area knowledge" (p. 31) when preparing students for agricultural communications.…”
Section: Agricultural Communications Educationmentioning
confidence: 99%
“…It is important to note that communications is central to a variety of human perceptions and behaviors, so it is natural that other disciplines and scholars would have occasional involvement in its conduct (Rogers & Chaffee, 1983). The fact that many agricultural communications graduate programs are relatively new and understaffed further necessitates involvement by faculty members from other disciplines, such as agricultural education, for service on graduate committees and related activities (Boone, Paulson, & Barrick, 1993). However, there is little evidence in the literature that agricultural communications research has been influenced in any direct way from the discipline of agricultural education compared to other social sciences (Boone et al, 2000;NPAC, 1960).…”
Section: Home Department Influencesmentioning
confidence: 99%
“…Over time, however, competencies needed for professional agricultural communications careers have changed with technology and job requirements (Rudd & Sprecker, 1997). In a study of graduate programs, Boone, Paulson, and Barrick (1993) found that graduate students in agricultural communications were educated in human relations, agricultural subject matter, communications skills, and communications systems. Reisner (1990) found that the most predominant characteristic of academic programs in agricultural communications was variety.…”
Section: Characteristics Of Agricultural Communications As a Professimentioning
confidence: 99%